Neodymium:yttrium-aluminum garnet capsulotomy rates after combined cataract surgery with implantation of a 4% water content hydrophobic acrylic intraocular lens and vitrectomy - Kabata Y (Dove Medical Press, 2013)
Yoshiaki Kabata,1 Genichiro Takahashi,1 Hiroshi Tsuneoka21Department of Ophthalmology, Jikei University School of Medicine, Katsushika Medical Center, 2Department of Ophthalmology, Jikei University School of Medicine, Tokyo, JapanBackground: The purpose of this study was to examine neodymium:yttrium-aluminum garnet (Nd:YAG) capsulotomy rates after combined cataract surgery with implantation of a three-piece 4% water content hydrophobic acrylic intraocular lens (X-70, Eternity®) and vitrectomy, and compare diabetic retinopathy with nondiabetic retinopathy.Methods: Nd:YAG capsulotomy rates were evaluated for 72 eyes of 72 patients with diabetic retinopathy and 81 eyes of 81 patients with nondiabetic retinopathy (50 eyes with retinal detachment, 13 eyes with macular hole, nine eyes with epiretinal membrane, seven eyes with branch retinal vein occlusion, and two eyes with uveitis) who underwent combined cataract surgery and vitrectomy and implantation of X-70.Results: Two years after combination surgery, four of 72 eyes (5.6%) in the diabetic retinopathy group and four of 81 eyes (5.0%) in the nondiabetic retinopathy group required Nd:YAG capsulotomies. Kaplan–Meier survival analysis showed no statistically significant differences between the two groups (P=0.30, Mantel–Cox log-rank test).Conclusion: The rate of Nd:YAG capsulotomy did not significantly differ between diabetic retinopathy and nondiabetic retinopathy after combined cataract surgery with implantation of the X-70 and vitrectomy. X-70 is an acceptable intraocular lens for patients undergoing combined cataract surgery and vitrectomy.Keywords: Nd:YAG capsulotomy rates, combined surgery, diabetic retinopathy, hydrophobic acrylic intraocular lens